Restraints and Propositions for Vegetable production in Ranga Reddy district of Telangana - V.V.S.S. Anusha; S.R. Padma (Journal of Agricultural Extension Management, 2021)
Ranga Reddy district is a peri-urban area cultivating vegetables. Vegetable growers in the area expressed dissatisfaction with their economic situation. This study was taken up to analyse the constraints faced by respondents to give a clear picture of the current scenario. Purposive sampling of mandals and villages followed by proportionate sampling led to a sample size of 150 respondents, who were contacted and data collected using a structured interview schedule. This study highlighted that unavailability of labour was the major production-related constraint and price fluctuation was the foremost market-related constraint. Suggestions by the respondents to uplift their economic situation included implementing minimum support price and exploring new marketing systems such as Retail marketing. In addition, they suggested that post-harvest infrastructure development like transport, storage, processing activities, promotion of export activities need to be focused on